2000
DOI: 10.1191/026921600669298725
|View full text |Cite
|
Sign up to set email alerts
|

The use of steroids in the management of inoperable intestinal obstruction in terminal cancer patients: do they remove the obstruction?

Abstract: This multicentre, randomized double-blind study was undertaken to assess the efficacy of corticosteroids as a palliative treatment of intestinal obstruction due to advanced and incurable cancer. Thirty-one French palliative care units agreed to participate in the study and 12 actually recruited at least one patient. To be included, patients had to have an advanced cancer with a surgically inoperable bowel obstruction and to have received no specific anticancer therapy within the preceding 28 days. They had to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 16 publications
1
42
1
3
Order By: Relevance
“…Median survival for patients with an ECOG score of 0-1 (n ¼ 15) was 222 days, which is much higher than the predicted 1-to 3-month survival that is expected with a diagnosis of MBO [4][5][6][7][8][9]. However, perhaps the most important information that this study has generated is the attenuated survival for patients with an ECOG score of 2 despite the fact that 7/9 patients received further treatment.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Median survival for patients with an ECOG score of 0-1 (n ¼ 15) was 222 days, which is much higher than the predicted 1-to 3-month survival that is expected with a diagnosis of MBO [4][5][6][7][8][9]. However, perhaps the most important information that this study has generated is the attenuated survival for patients with an ECOG score of 2 despite the fact that 7/9 patients received further treatment.…”
Section: Discussionmentioning
confidence: 79%
“…Prolonged survival was demonstrated for select patients with an ECOG score of 0/1 and who were able to receive either surgery and/or chemotherapy as opposed to supportive care only with two patients living over 800 days (one had surgery alone, one had chemotherapy and surgery) compared to the reported median survival of 3 months of patients with non-curative cancer and a MBO [4][5][6][7][8][9]. We and others have previously demonstrated that patients who are able to receive palliative chemotherapy do have a prolonged survival and that surgery can act as a bridge to palliative chemotherapy [10] [11].…”
Section: Discussionmentioning
confidence: 96%
“…Laval et al 14 reported a randomized double-blind prospective study in patients with MBO. In this study, methylprednisolone 40 or 240 mg was administered once a day intravenously over 1 hour for 3 days.…”
Section: 13mentioning
confidence: 99%
“…Outcomes were not statistically significant and because of the small sample size, no conclusion was made regarding dosage and efficacy. 14 Laval et al 15 recommended use of steroids in peritoneal carcinomatosis with a dose of 1-4 mg/kg/day methylprednisolone and 0.25-1 mg/kg/day dexamethasone once a day intravenously or subcutaneously for a short course (5-10 days). They suggested steroids be started at the time of diagnosis and continued if symptoms improve or with resolution of bowel obstruction.…”
Section: 13mentioning
confidence: 99%
“…For patients with recurrent obstruction and advanced disease, medical management of symptoms is preferable [SORT B]. 33 Colicky pain responds to antispasmodic agents. Opioids relieve constant pain but also decrease peristalsis, which contributes to constipation.…”
Section: Emergent Visceral Pain Syndromesmentioning
confidence: 99%